Subfunctionalization probably drives the emergence of plant growth‑promoting genes - Frare, Romina Alejandra (2022)
The duplication and divergence of stress-related genes might help microbes adapt to different environments. However, little is known about this type of subfunctionalization process in microbes. We here examined the evolution and function of PHB polymerases (PhaCs) from the plant growth-promoting, endophytic, and diazotrophic bacterium Azospirillum brasilense Az39. Besides the previously reported chromosomal phaC gene (phaCAz39-Chr) involved in abiotic stress adaptation, we showed that strain Az39 contains an additional copy of the phaC gene (phaCAz39-p4) in an extra-chromosomal replicon. Heterologous expression analysis demonstrated that the phaCAz39-p4 gene codifies for a functional PHB polymerase. Comparative sequence and evolutionary analyses showed an extreme level of divergence between PhaCAz39-p4 and other known PhaCs, including PhaCAz39-Chr, suggesting a divergent evolution of paralogous copies of phaC from strain Az39. Contrary to its paralogous copy, phaCAz39-p4 is specifically induced in planta and is necessary to enhance plant growth, thus empirically supporting the predicted functional divergence.